Archaeologists in print Publishing for the people - Thornton, Amara (UCL Press, 2018)
Archaeologists in Print is a history of popular publishing in archaeology in the nineteenth and twentieth centuries, a pivotal period of expansion and development in both archaeology and publishing. It examines how British archaeologists produced books and popular periodical articles for a non-scholarly audience, and explores the rise in archaeologists' public visibility. Notably, it analyses women's experiences in archaeology alongside better known male contemporaries as shown in their books and archives. In the background of this narrative is the history of Britain's imperial expansion and contraction, and the evolution of modern tourism in the Eastern Mediterranean and Middle East. Archaeologists exploited these factors to gain public and financial support and interest, and build and maintain a reading public for their work, supported by the seasonal nature of excavation and tourism. Reinforcing these publishing activities through personal appearances in the lecture hall, exhibition space and site tour, and in new media - film, radio and television - archaeologists shaped public understanding of archaeology. It was spadework, scripted.